Pelatihan Kanban dengan Permainan Simulasi pada Industri Percetakan Sablon - Suparno, Adizty; Koeswara, Sonny; Chandra, Agung (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2024)
This community service aims to build a problem-solving mindset in screen printing companies, regarding the implementation of kanban. Currently, all roles in the company are expected to have ideas for solving problems. To generate a more structured productive mindset in the future, we need a facility that can free up ideas and provide feedback on decisions starting from the company's board of directors down to employee level. By implementing training that is equipped with simulations of case examples, the service team aims to improve the mindset of all workers that by implementing kanban simulations can be used as a strategy to achieve an agile manufacturing company. It is hoped that developing this mindset can awaken all workers to contribute to each of their work responsibilities.